The Outcome of Patients on the Cholecystectomy Waiting List in Western Australia 1999-2005. - Epari, K.; Mukhtar, Syed Aqif; Fletcher, D.; Samarasam, I.; Semmens, James (Wiley-Blackwell Publishing Asia, 2010)
Surgeons are noticing increasing numbers of cholecystectomy waiting list patients presenting with complications of their gallstones. In this study we analyzed the outcome of these to ascertain natural history and outcome. Data for 5,298 waiting list patients in Western Australian from 1999 to 2006 were analysed. Negative Binomial Regression was used to analyse waiting times data with Waitlist Year, Urgency Category and Aboriginality, after adjusting for Gender, Location and Age at Cholecystectomy. The overall median waiting time for surgery was 40 days (IQR=15-103). The median waiting times for Urgent, Semi-Urgent, and Routine categories were 21(IQR=8-63), 44(IQR=20-97) and 50(IQR=17-131) days respectively. While waiting for surgery, 240(5%) patients had gallstone-related admissions. Eighty (33.3%) patients had previous gallstone-related admissions prior to their enrolment on the waiting list. Analysis of the crude odds ratio showed that the probability of readmission during wait for surgery was three times more, when the surgery was not performed within the recommended time. Aboriginal and Torres Strait Islanders wait 1.77 times longer than non aboriginals (p<0.001) and waiting time decreased with more recent calendar years. (p=0.001) Patients in the metropolitan hospitals waited twice as long compared to the regional hospitals (p<0.001). Approximately 5% of patients on the waiting list for an elective cholecystectomy were readmitted to the hospital for gallstone-related problems. Proper categorisation of patients and definitive surgical treatment of acute gallbladder disease at index presentation might decrease this readmission rate. More effort needs to be made to ensure equity of access for gallstone patients.